Circular Economy: A New Horizon for Bio-Nanocomposites from Waste Materials - Morganti, Pierfrancesco (International Journal of Biotechnology for Wellness Industries, 2021)
Circular Economy [1] will offer a major opportunity to increase resource productivity, decrease consume and waste dependence, offering the opportunity to create new employment and growth. At this purpose, today, science provides evidence that this new economical vision, enabled by the bio-nanotechnology revolution, could generate by 2030 to Europe's economy, a primary resource benefits of as much as € 0.6 trillion per year [1,2]. In addition and under the anchor points of the EU normative (Figure 1) [3], it could generate €1.2 trillion in non-resource and externality benefits, bringing the annual total benefits to around €1.8 trillion versus to day [1,2]. Thus, the necessity to increase the resource efficiency, use agricultural and industrial by-products as raw materials, and minimize both greenhouse gas emissions (GHGs) and waste, for reducing the fossil-based products and maintaining the human wellbeing and the environment biodiversity.